Lump Solutions of a Nonlinear PDE Combining with a New Fourth-Order Term Dx2Dt2∗. (1st February 2020) - Zhang, Liqin; Ma, Wen-Xiu; Huang, Yehui
Abstract : A nonlinear PDE combining with a new fourth-order term D x 2 D t 2 is studied. Adding three new fourth-order derivative terms and some second-order derivative terms, we formulate a combined fourth-order nonlinear partial differential equation, which possesses a Hirota's bilinear form. The class of lump solutions is constructed explicitly through Hirota's bilinear method. Their dynamical behaviors are analyzed through plots.